2019
DOI: 10.1172/jci.insight.126337
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory IL-17 pathways dominate the architecture of the immunome in pediatric refractory epilepsy

Abstract: Drug refractory epilepsy (RE) is a chronic neurological disease with varied etiology that represents a group of patients whose seizures do not respond to antiepileptic drugs. The immune system may have a role in seizure and epilepsy development, but the specific mechanisms of inflammation that lead to epileptogenesis and contribute to RE are unknown. Here, we used mass cytometry to comprehensively study the immune system of pediatric patients with RE and compared their immune profile and function with patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Accordingly, we found that the frequency of proinflammatory CD4 T cells expressing Th17/Th1‐related cytokines is higher in the peripheral blood of epilepsy and DRE patients, in line with previous reports in pediatric DRE 40,41 and in adult temporal lobe epilepsy 38 . Similar to a recent study in autoimmune epilepsy in children, we did not observe a concomitant increase in expression of Th17‐related surface markers CCR6 and CD161 42 . However, we did observe a higher frequency in epilepsy subjects of CD4 T cells expressing MCAM, a cell adhesion molecule associated with transmigration of proinflammatory Th17/Th1 cells toward the CNS compartment in multiple sclerosis 19 .…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, we found that the frequency of proinflammatory CD4 T cells expressing Th17/Th1‐related cytokines is higher in the peripheral blood of epilepsy and DRE patients, in line with previous reports in pediatric DRE 40,41 and in adult temporal lobe epilepsy 38 . Similar to a recent study in autoimmune epilepsy in children, we did not observe a concomitant increase in expression of Th17‐related surface markers CCR6 and CD161 42 . However, we did observe a higher frequency in epilepsy subjects of CD4 T cells expressing MCAM, a cell adhesion molecule associated with transmigration of proinflammatory Th17/Th1 cells toward the CNS compartment in multiple sclerosis 19 .…”
Section: Discussionsupporting
confidence: 92%
“…In neurology, IL-17A has been found to be increased in MS and related disorders but also in NMDAR encephalitis and refractory epilepsy (RE) (15,27). Kumar et al reported a similar immune profile between children with RE and Rasmussen's encephalitis with expansion of CD4+ IL17+ T cells and expansion of CD25+ B cells suggesting that both Th17 and B cells are involved in the pathogenesis of RE and AE (27). However, epilepsy in patients with NIND does not result in a high level of CSF IL-17A or IL-6 as compared to immune-mediated epilepsy in the elderly (28).…”
Section: Discussionmentioning
confidence: 99%
“…A major portion of this process is the inflammatory response, and changes in the inflammatory factors to a certain extent indicate that the occurrence of epilepsy can also induce a certain inflammatory response. For instance, IL-1β, IL-6, IL-10, IL-2, IL-17 ( Kumar et al, 2019 ), IL-4, and TNF-α were abnormally expressed in patients, whose elevated levels can lead to neuronal degeneration and induce epilepsy ( Ravizza et al, 2006 ). Another mechanism by which IL-1 participates in epilepsy is through the upregulation of NMDA receptors on postsynaptic cells through the activation of GluN2B subunits of NMDA receptors ( Ravizza et al, 2006 ).…”
Section: The Pathogenesis Of Epilepsymentioning
confidence: 99%